Pancreatic ductal adenocarcinoma: the latest on diagnosis, molecular profiling, and systemic treatments - Bugazia, Doaa; Al-Najjar, Ebtesam; Esmail, Abdullah; Abdelrahim, Saifudeen; Abboud, Karen; Abdelrahim, Adham; Umoru, Godsfavour; Rayyan, Hashem A.; Abudayyeh, Ala; Al Moustafa, Ala-Eddin; Abdelrahim, Maen (Frontiers in Oncology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is currently the fourth leading cause of death in the United States and is expected to be ranked second in the next 10 years due to poor prognosis and a rising incidence. Distant metastatic PDAC is associated with the worst prognosis among the different phases of PDAC. The dDiagnostic options for PDAC that are convenient and available for staging, tumor response evaluation, and management of resectable or borderline resectable PDAC. However, imaging is crucial in PDAC diagnosis, monitoring, resectability appraisal, and response evaluation. The advancement of medical technologies is evolving, hence the use of imaging in PDAC treatment options has grown as well as the utilization of ctDNA as a tumor marker. Treatment options for metastatic PDAC are minimal with the primary goal of therapy limited to symptom relief or palliation, especially in patients with low functional capacity at the point of diagnosis. Molecular profiling has shown promising potential solutions that would push the treatment boundaries for patients with PDAC. In this review, we will discuss the latest updates from evidence-based guidelines regarding diagnosis, therapy response evaluation, prognosis, and surveillance, as well as illustrating novel therapies that have been recently investigated for PDAC, in addition to discussing the molecular profiling advances in PDAC.